Old Pathways, New Directions: Using Lived Experiences to Rethink Classroom Management (LEARNing Landscapes, 2012)
Two stories lived and told become an entry point towards reflecting on issues of teacher practice related to classroom management. Using a narrative inquiry approach, personal experiences with Michael and Carlton—two kindergarten students—are pivotal in developing a deeper understanding of the difference between punitive and instructive discipline. Drawing on the philosophies of Vivian Paley, the reader is left with creative possibilities for new directions in attending to children’s unmet needs and, at the same time, ideas for facilitating a supportive and inclusive classroom environment for all learners.
Keywords: teacher practice; classroom management; narrative inquiry; kindergarten student; classroom environment; creativity